Uji Komparasi Instrumen Arah Kiblat Antara Qibla Tracker dan Mizwala Qibla Finder - Maulidin, Maulidin; Abdullah, Abdullah (Islamic Astronomy Department, Sharia and Law Faculty, 2022)
People often face problems and problems related to the direction of the Qibla. So far, the measurement of the direction of the Qibla in most methods always uses the Sun, the Sun is one of the celestial bodies that can be used as a reference to measure the direction of the Qibla either in the shadow of the Sun or the azimuth of the Sun. From the help of the Sun, many qibla direction instruments were born such as the Mizwala Qibla Finder and Qiblat Tracker. In this case the author wants to test the accuracy of both instruments with the help of theodolites. To find out the extent of the accuracy of the results of measuring the direction of the Qibla with the instrument, the author formulated several research questions. 1 what is the qibla direction measurement technique using Mizwala Qibla Finder and Qibla Tracker? 2 how is the accuracy rate of Qibla direction using Mizwala Qibla Finder and Qibla Tracker? To answer these research questions, the author uses a qualitative research method with an astronomical approach, the primary data used is in the form of the results of a trial measurement of qibla direction with Mizwala Qibla Finder and Qibla Tracker. Based on the results of research conducted by comparing two instruments, namely Qibla Tracker and Mizwala Qibla Finder, it can be concluded that Mizwala Qibla Finder is the first place compared to Qibla Tracket with a difference of 00 1' 37.43